Fracture of laminated bamboo and the influence of preservative treatments. (1st October 2019) - Reynolds, Thomas P.S.; Sharma, Bhavna; Serrano, Erik; Gustafsson, Per-Johan; Ramage, Michael H.
Abstract: Treated bamboo can be made into large, durable structural elements which have the potential to become a transformative large-scale building material, but the fracture behaviour which determines their ultimate strength in various loading scenarios has not been studied. Laminated bamboo is a promising structural engineered bamboo material, and is generally made from bamboo treated to improve its durability. Studies into the structural behaviour of laminated bamboo indicate that different preservative treatments affect the structural properties of the composite differently, with conflicting evidence from tests in different load orientations. This study uses fracture mechanical testing and microscopy to develop an understanding of the fracture mechanics of engineered bamboo, and explains why the properties of the composite under tension, compression and bending may be affected differently by the treatment processes. Two types of treated Moso bamboo are studied alongside the same material with minimal processing. The treated material had gone through one of two commercial processes: bathing in a hydrogen peroxide bleach solution, or treatment by pressurised steam (described as caramelised). The results show that the critical strain energy release rate in the caramelised material is much lower than that in the bleached, and the fracture behaviour of the bleached material is closer to that of the raw bamboo. Fracture experiments included Mode I and Mode II fracture with cracks progressing parallel to the grain, and Mode I fracture with a crack progressing perpendicular to the grain. The results shed new light on the strength of structural-size elements.